Analisis Penerapan Akuntansi pada Usaha Mikro Kecil dan Menengah (UMKM) MD Ponsel - Ajeng Manjana; Tri Inda Fadhila Rahma; Nursantri Yanti (Journal on Education, 2023)
This study aims to find out how the preparation and recording of financial reports made by MD Ponsel and to find out the application of accounting in MD Ponsel's micro, small and medium enterprises. This study uses a data analysis method in the form of a qualitative approach with the type of case study research. The object of this research is the business manager of MD Ponsel Kota Datar. MD Ponsel has financial records which are a book of cash receipts for sales and also disbursements of cash for purchases of supplies, payment of employee salaries, payment of electricity and others, besides that MD Ponsel can be said to have made financial reports in the form of profit and loss but not yet in accordance with SAK-EMKM . The most important obstacle faced by MD Ponsel is the lack of understanding of business owners and employees in preparing proper financial reports..